Phasing out energy subsidies as part of Egypt’s economic reform program: Impacts and policy implications - Breisinger, Clemens; Mukashov, Askar; Raouf, Mariam; Wiebelt, Manfred (International Food Policy Research Institute, 2018)
In order to address long-standing economic challenges, in 2016 the Government of Egypt (GOE) put in place a major economic reform program to restore macroeconomic stability and to promote inclusive growth. As a result, there are early signs that the economy is rebounding and Egypt’s economic outlook is becoming more favorable. However, it is less clear how the ongoing reform program is affecting households, especially the poor. To shed light on this question, this paper uses an economy-wide model to estimate the distributional impacts of the energy subsidy cuts in 2014, 2016, and 2017, the currency devaluation at the end of 2016, and the expected complete phasing out of energy subsidies over the coming years.